The Archean Victoria Fjord terrane of northernmost Greenland and geodynamic interpretation of Precambrian crust in and surrounding the Arctic Ocean. (September 2019) - Nutman, Allen P.; Bennett, Vickie C.; Hidaka, Hiroshi; Henriksen, Niels; Ali, Sarmad
Graphical abstract: Highlights: The Victoria Fjord terrane, is a unique Archean exposure in far north Greenland. It consists of Palaeoarchaean granitoids with <2.71 Ga sedimentary rocks. Its early evolution resembles continental crust in the Arctic Ocean and Eastern Siberia. Its Archean evolution is distinct from the rest of Greenland. Abstract: In far North Greenland at the head of Victoria Fjord (∼81°30′N), a ∼1000 km 2 exposure of Precambrian crystalline basement rocks is a window through the region's extensive latest Neoproterozoic and Paleozoic Arctic Platform sedimentary cover sequence. These basement rocks, named here the Victoria Fjord terrane, are dominated by weakly-foliated granodioritic orthogneisses, with lesser amounts of migmatite. These are intercalated with strips of supracrustal rocks dominated by paragneisses. This poorly-exposed Archean terrane at Greenland's northern tip is succeeded to the south by the extensive east-west trending Paleoproterozoic Inglefield Mobile Belt of juvenile arc rocks. The Victoria Fjord terrane granodiorites have zircon U-Pb ages from 3292 ± 14 Ma to ∼3260 Ma. Reconnaissance U-Pb dating on schlieric migmatite zircons yielded ages of ∼3280, 3400 and 3500 Ma. Paragneiss detrital zircons have ages of mostly ∼2710 Ma, with a minority of 3000–2900 Ma grains. This demonstrates that these sedimentary rocks were not derived from the local basement. Post- Archean magmatic or metamorphic zircon was not detected in any of the samples. Initial εHf of 3290–3260 Ma granodiorite and granite zircons ranges from −4 to +2, and the magmatic protoliths are interpreted as sourced from the melting of somewhat older (3500–3400 Ma) Paleoarchean crust, represented by paleosome in the migmatites. The paragneiss 3000–2900 Ma detrital zircons were derived from juvenile felsic crust of that age. The ∼2710 Ma group show negative correlation of Th/U and initial εHf, such that those with high Th/U up to >2.0 have εHf values of −6 to −10. The ∼2710 zircons were sourced from mafic rocks formed by melting of much older (Paleoarchean?) enriched mantle which was variably contaminated by 3000–2900 Ma crust during its ascent. The Victoria terrane is unique amongst the Archean basement terranes in Greenland because it is dominated by 3500–3260 Ma crust. However, the Arctic basin contains detrital zircons of that age, and rocks of that age also occur in eastern Siberia and northwestern Canada. Implications for high Arctic early Precambrian geodynamics are discussed.